2014
DOI: 10.1038/cddis.2014.305
|View full text |Cite
|
Sign up to set email alerts
|

miR-17 extends mouse lifespan by inhibiting senescence signaling mediated by MKP7

Abstract: Here we show that transgenic expression of miR-17 extends lifespan and inhibits cellular senescence. We propose that miR-17 acts as a critical regulator of cellular senescence and tumorigenesis. We demonstrate that miR-17 targets both ADCY5 and IRS1, upregulating the downstream signals MKP7, FoxO3, LC3B, and HIF1α, and downregulating mTOR, c-myc, cyclin D1, and JNK. Silencing either ADCY5 or IRS1 promoted autophagy and repressed cellular senescence and apoptosis. Repression of ADCY5 by miR-17 translocated memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 47 publications
(56 reference statements)
5
33
0
Order By: Relevance
“…Moreover, the autophagic activation by anti‐miR‐17 decreases the threshold of temozolomide resistance in T98G cells . MiR‐17 also targets both ADCY5 and insulin receptor substrate 1 to promote autophagy and repress cellular senescence and apoptosis …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the autophagic activation by anti‐miR‐17 decreases the threshold of temozolomide resistance in T98G cells . MiR‐17 also targets both ADCY5 and insulin receptor substrate 1 to promote autophagy and repress cellular senescence and apoptosis …”
Section: Discussionmentioning
confidence: 99%
“…As shown in figure 3b, inhibition of mTOR by miR-17-5p upregulates autophagy and slows down the aging process in the mouse model presented by Du et al [28], discussed in the section A Long-Lived Pre-miR-17 Overexpressing Mouse Model. Indeed, oncogenic miRNAs like miR-17 are upregulated in rapamycin-resistant cells and inhibition of miR-17 restored rapamycin sensitivity.…”
Section: Aging the Mir-17-92 Cluster And Mir-17-5pmentioning
confidence: 99%
“…The interest in the role of miR-17-5p in aging research has peaked with the report that its overexpression in mouse extends the organismal lifespan by approximately 16% [28]. This finding was somewhat surprising after the same authors had previously observed that miR-17 represses fibronectin expression, leading to cellular defects, growth retardation, smaller organs and strongly reduced hematopoietic cell lineages in miR-17-overexpressing mice [29], results that do not seem well reconciled yet.…”
Section: Aging the Mir-17-92 Cluster And Mir-17-5pmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence shows that abnormal expression of miRNAs in tumors can lead to changes in the intrinsic properties of cancer cells, which include cell proliferation, migration, apoptosis, and cellular senescence. 1 Recent research from our lab has implicated the importance of miR-17 expression in the adaptability of tumor cells to environmental fluctuations using the glioblastoma cell line. These cells, which are highly adaptive and over-express miR-17, appeared to adopt a new strategy to cope with the lack of nutrition in the environment by lowering their metabolic rate.…”
mentioning
confidence: 99%